Pollution and health risk assessment of co-existing microplastics and heavy metals in urban dust of Riyadh city, Saudi Arabia - Ahmad, Munir; Al-Swadi, Hamed Ahmed; Ahmad, Jahangir; Akanji, Mutair A.; Mousa, Mohammed Awad; Lubis, Nahrir M.A.; Al-Wabel, Mohammad I.; Al-Farraj, Abdullah S. F. (Frontiers in Environmental Science, 2024)
Microplastics (MPs) and heavy metals have recently attracted much attention due to their widespread distribution in the environment. Co-occurrence of MPs and heavy metals in dust poses potential health risks for humans. The objectives of this study were to investigate pollution and health risk factors associated with co-occurring MPs and heavy metals in urban dust. Here, 20 dust samples (both indoor and outdoor environments) were collected from different places in Riyadh, Saudi Arabia using sweeping method. The MPs were separated from dust samples via density separation using ZnCl2 Microscopic techniques were used to investigate MPs while inductively coupled plasma optical emission spectrometry was used heavy metals analyses in the collected samples. The results of the study showed that all the collected dust samples were contaminated with MPs of different shapes, sizes, and colors. Fragment-shaped MPs were the most dominant, followed by granules, fibers, and lines, while the majority of the MP particles were red and black. Furthermore, the size distribution analyses demonstrated that particles above 1000 µm were abundant. Also, the number of MPs was in the range of 20 particles g-1 to 1052 particles g-1. Human exposure estimations showed that toddlers could inhale more MPs (0.86 MPs particles kg-1 day-1 and 312.93 particles kg-1 year-1) than children, teenagers, and adults. In addition, the concentrations of heavy metals varied from one site to another, however, the average concentrations were lower than their corresponding values in the guidelines (except for Zn). The integrated potential ecological risk in dust samples was characterized as a low-risk criterion. The enrichment factor for Zn in dust samples at all sites was more than 2, indicating a major contamination concern and anthropogenic sources responsible for the existence of Zn. The estimated hazard quotient indicates that children and adults are saved from the adverse effects of dust inhalation in the studied area. These findings could serve as a preliminary step for efficient pollution management and environmental quality maintenance in Riyadh.